2013
DOI: 10.2134/jeq2012.0356
|View full text |Cite
|
Sign up to set email alerts
|

Use of Standardized Procedures to Evaluate Metal Leaching from Waste Foundry Sands

Abstract: As part of the casting process, foundries create sand molds and cores to hold the molten metal to specifi c dimensional tolerances. Although most of the waste foundry sands (WFSs) from this process are land fi lled, there is great interest in diverting them for use in agricultural and geotechnical applications. One potential limitation to their benefi cial use is concern that the WFSs will leach high levels of trace metals. Th e aim of this study was to quantify Ag, Ba, Cd, Cr, Cu, Ni, Pb, and Zn in leaching e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The TCLP test has been applied to numerous WFSs; and in almost all cases, sands from iron, steel, and aluminum foundries were not determined to be toxic (Deng 2009;Miguel et al 2013). The leaching results were also compared to groundwater MCLs ( (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…The TCLP test has been applied to numerous WFSs; and in almost all cases, sands from iron, steel, and aluminum foundries were not determined to be toxic (Deng 2009;Miguel et al 2013). The leaching results were also compared to groundwater MCLs ( (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Research to date, however, has demonstrated that many WFSs are not hazardous, as metal concentrations in leaching extracts were reported to be below regulatory thresholds [4][5][6]. These results are not surprising since total metal concentrations in waste sands from iron, steel, and aluminum foundries fall within ranges found in native surface soils [7].…”
Section: Introductionmentioning
confidence: 98%
“…Numerous researches have been carried out on the composition of residual sand. The results of the experiments showed that the residual foundry sand is a new material, with a modified composition, compared to fresh sand [3][4][5][6][7][8][9][10][11]. Most foundry sands are non-hazardous waste, but environmental authorities are often reluctant to allow their beneficial use in agricultural and geotechnical applications due to metal leaching concerns.…”
Section: Introductionmentioning
confidence: 99%